Key competences and plurilingual education in the Valencian Region (Spain): A curricular analysis of Primary Education - Cerezo Herrero, Enrique; Romeu Peiró, María Candelaria; Grao Rodríguez, Almudena (Pulso. Revista de educación, 2020)
The purpose of this work is to study the level of transversality of key competences in Primary Education in the Valencian Community. To this end, an analysis of the Decree 108/2014 currently in effect will be carried out, along with determining the frequency with which each competence is worked on during this stage of education. The data obtained will be interpreted bearing in mind plurilingual programs and, more specifically, the basis of the methodological needs that are pursued in CLIL, the approach to teaching non-linguistic areas through a foreign language. Generally, the findings point to a lack of transversality in some of the competences, one of them being the linguistic competence. This implies the need for a more cross-curricular competence model for plurilingual education, since the rigid structure of the key competences in the current curriculum and, therefore, the lack of a greater interconnection among them may hinder to a great extent the proper functioning of the principles that the CLIL approach posits.